Possibilidades de trabalhar conteúdos matemáticos com origamis - Graciolli, Carolina Yumi Lemos Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
In this text we present a research that seeks to understand the production of geometric knowledge of the student from the work with origami. In the readings we realize that mathematics has a strong connection with origami and because it is a visual resource it can make possible the understanding of mathematics, because it favors the investigation, the construction of arguments and the justifications allowing the subject to understand the mathematical sense. We assume as methodology the case study and the phenomenology analysis for the interpretation of the data produced. We developed in an Euclidian Geometry class the activity that involved origami and a classic problem of geometry, the trisection of the angle, with students of the third year of the Mathematics Degree course of the São Paulo State University (Unesp), School of Engineering, Guaratinguetá. The intention of the activity was to see how students explore mathematics when they use origami to solve situations involving mathematical contents, what knowledge they expose and what strategies they use. With the analysis of the data we conclude that, in this specific group, students produce geometric knowledge when working with origami when they argue about what is done and investigate possibilities to do

Neste texto apresentamos uma pesquisa que busca compreender a produção do conhecimento geométrico do aluno a partir do trabalho com origami. Nas leituras percebemos que a matemática tem uma forte conexão com o origami e por ser um recurso visual poderá possibilitar a compreensão da matemática, pois favorece a investigação, a construção de argumentos e as justificativas, permitindo ao sujeito compreender o sentido matemático. Assumimos como metodologia o estudo de caso e a análise fenomenologia para a interpretação dos dados produzidos. Desenvolvemos em uma aula de Geometria Euclidiana a atividade que envolvia o origami e um problema clássico da geometria, a trissecção do ângulo, com alunos do terceiro ano do curso de Licenciatura em Matemática da Universidade Estadual Paulista Júlio de Mesquita Filho, campus Guaratinguetá. A intenção da atividade foi ver como os alunos exploram matemática quando utilizam o origami para resolver situações problemas que envolvem conteúdos matemáticos, quais conhecimentos expõem e a quais estratégias recorrem. Com a análise dos dados concluímos que, neste grupo especifico, os alunos produzem conhecimento geométrico quando trabalham com o origami no momento em que argumentam sobre o que é feito e investigam possibilidades de fazer
Keywords: Matemática - Estudo e ensino; Trissecção do ângulo; Geometria - Estudo e ensino; Origami; Mathematics Study and teaching